Comparative evaluation of different types of anesthesia in surgical treatment of children with congenital defects - О.О. Vlasov (Medičnì Perspektivi)
In pediatric anesthesiology in surgical interventions various methods of combined anesthesia with a combination of inhalation, regional, and intravenous anesthesia are used. The provision of high-quality anesthetic support in newborns and infants during surgical treatment of congenital defects is complicated by risk factors, concomitant diseases and different pathology conditions. The study of risk factors and their influence on the functional indices of the child's vital activity in prescribing anesthesia at all stages of the surgical intervention will help prevent complications and deaths in children. Aim – to сonduct a comparative assessment of various types of anesthesia for surgical correction of congenital defects in children and create a predictive model of the association of risk factors and deaths in the selected methods of anesthetic support. The retrospective study included 150 newborns and infants with congenital defects of the surgical profile depending on anesthesia (inhalation + regional anesthesia; inhalation + intravenous anesthesia and total intravenous). After identifying and evaluating prognostic variables by simple logistic regression with calculating the odds ratio, stepwise multiple logistic regression analysis was performed and a predictive model of the association of risk factors and deaths with various types of anesthetic management was created. In thoracic operations a combined anesthesia with sevoran and fentanyl was most often used – 20.4%. In abdominal operations, in total anesthetic support with sevoran and regional anesthesia was used– 69.4%, while in urological operations combined total intravenous anesthesia with 2 drugs – 18.4% ranked first. No significant differences were found between the types of anesthesia in various surgical interventions for congenital pathologies, between the types of surgery and deaths (p = 0.863). To prevent fatalities in various types of surgical intervention and options for anesthetic support of newborns and infants with congenital defects, it is advisable to more closely monitor the cerebral and peripheral oximetry indicators at all stages of treatment and timely correct the impaired condition of the child.